A novel PI3K inhibitor XH30 suppresses orthotopic glioblastoma and brain metastasis in mice models - Ming Ji; Dongjie Wang; Songwen Lin; Chunyang Wang; Ling Li; Zhihui Zhang; Jing Jin; Deyu Wu; Yi Dong; Heng Xu; Duo Lu; Xiaoguang Chen (Elsevier, 2022)
Glioblastoma is carcinogenesis of glial cells in central nervous system and has the highest incidence among primary brain tumors. Brain metastasis, such as breast cancer and lung cancer, also leads to high mortality. The available medicines are limited due to blood-brain barrier. Abnormal activation of phosphatidylinositol 3-kinases (PI3K) signaling pathway is prevalent in glioblastoma and metastatic tumors. Here, we characterized a 2-amino-4-methylquinazoline derivative XH30 as a potent PI3K inhibitor with excellent anti-tumor activity against human glioblastoma. XH30 significantly repressed the proliferation of various brain cancer cells and decreased the phosphorylation of key proteins of PI3K signaling pathway, induced cell cycle arrest in G1 phase as well. Additionally, XH30 inhibited the migration of glioma cells and blocked the activation of PI3K pathway by interleukin-17A (IL-17A), which increased the migration of U87MG. Oral administration of XH30 significantly suppressed the tumor growth in both subcutaneous and orthotopic tumor models. XH30 also repressed tumor growth in brain metastasis models of lung cancers. Moreover, XH30 reduced IL-17A and its receptor IL-17RA in vivo. These results indicate that XH30 might be a potential therapeutic drug candidate for glioblastoma migration and brain metastasis.